Tổng hợp thuốc chống sốt rét hydroxypiperaquin - Tuyến, Nguyễn Văn; Hùng, Nguyễn Văn (Vietnam Journal of Chemistry, 2014)
Piperaquine has been effectively used in combination with dihydroartemisinin for treatment of the CQ-resistant malaria in Vietnam. At present this compound is synthesized in our laboratory in multikilogram for making the artekin-drug for the treatment of malaria. In order to investigate the relationship between structure of piperaquine derivatives and the antimalarial activity and look for piperaquine analogs, here, we describe the synthesis of a piperaquine analog. Hydroxypiperaquine was synthesized by two methods. In the first method, hydroxypiperaquine was synthesized by treatment of two equivalents of 7-chloro-4-(piperazine-1-yl)quinoline (9) with one equivalent of epichlorohydrine in 50% yield. In the second one, the hydroxypiperaquine was obtained by reaction of 7-chloro-4-(piperazine-1-yl)quinoline (9) and 1-chloro-3[4-(7-chloroquinolin-4-yl)piperazin-1-yl]propan-2-ol (10) in 70% yield. The structures of the intermediates and hydroxypiperaquine were reconfirmed by IR, MS and NMR spectra.